1909 Me. Laws 169, An Act concerning the protection of children, ch. 166, § 2 - (:unkn) unknown (General Publisher, 1909)
Considered the transfer f firearms to children dangerous to the welfare of such children unless in circumstances where the child is being furnished the weapon for hunting or target shooting
--
Keywords: TRANSFER - MINORS